Improving women's knowledge about prenatal screening in the era of non-invasive prenatal testing for Down syndrome - development and acceptability of a low literacy decision aid - Sian Karen Smith; Antonia Cai; Michelle Wong; Mariana S. Sousa; Michelle Peate; Alec Welsh; Bettina Meiser; Rajneesh Kaur; Jane Halliday; Sharon Lewis; Lyndal Trevena; Tatiane Yanes; et al. (BMC, 2018)
Abstract Background Access to information about prenatal screening is important particularly in light of new techniques such as non-invasive prenatal testing (NIPT). This study aimed to develop and examine the acceptability of a low literacy decision aid (DA) about Down syndrome screening among pregnant women with varying education levels and GPs. Methods We developed a DA booklet providing information about first-trimester combined testing, maternal serum screening, and NIPT. GPs and women participated in a telephone interview to examine the acceptability of the DA and measure screening knowledge before and after reading the DA. The knowledge measure was designed to assess whether women had understood the gist of the information presented in the decision aid. It comprised conceptual questions (e.g. screening tells you the chance of having a baby with Down syndrome) and numeric questions (e.g. the accuracy of different screening tests). Results Twenty-nine women and 18 GPs participated. Regardless of education level, most women found the booklet 'very' clearly presented (n = 22, 76%), and 'very' informative (n = 23, 80%). Overall, women's conceptual and numeric knowledge improved after exposure to the DA, from 4% having adequate knowledge to 69%. Women's knowledge of NIPT also improved after receiving the decision aid, irrespective of education. Most GPs found it 'very' clearly presented (n = 13, 72%), and that it would 'very much' facilitate decision-making (n = 16, 89%). Conclusions The DA was found to be acceptable to women as well as GPs. A comprehensive evaluation of the efficacy of the decision aid compared to standard information is an important next step. Strategies are needed on how to implement the tool in practice.